PELAYANAN PUBLIK DALAM PERLINDUNGAN ANAK KABUPATEN MUSI RAWAS UTARA - Eva Kurnia Farhan; Mardi Murahman; Yulia Kartika (Jurnal PAsira, 2021)
ABSTRACT The research objective was to determine public services towards child protection in the Sector of Women Empowerment and Child Protection in the North of Musi Rawas District. The research method used is a qualitative descriptive research method. Data collection techniques in research through observation, data collection by interview, and data collection by documentation. Data analysis techniques are data reduction, data display, and conclusion drawing/verification. The results showed that achievement service protection towards child protection in North Musi Rawas Regency such as Tangible Dimensions, service user forms have clear standards, the ability of employees to use tools in the service process and counseling that are so urgently needed by the community can be fulfilled optimally. The Assurance dimension has been fulfilled by providing a sense of trust as a guarantee to the community. The empathy dimension, this dimension provides good communication, sincere and individual attention, and responsiveness given to service recipients by trying to understand service providers are expected to have an understanding and knowledge of service users, understand the specific needs of service users, and to know and understand the needs of the service recipient. Keywords: Public Service; Children Protection ABSTRAK Tujuan penelitian untuk mengetahui pelayanan publik dalam perlindungan anak di Bidang Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Musi Rawas Utara. Penelitian yang digunakan adalah Metode penelitian bersifat deskriptif kualitatif. Teknik pengumpulan data dalam penelitian dengan observasi, pengumpulan data dengan wawancara dan pengumpulan data dengan dokumentasi. Teknik analisis datanya adalah Data reduction (reduksi data), Data display (penyajian data) dan Data conclusion drawing/ verification. Hasil penelitian menunjukan bahwa terwujudnya perlindungan anak di Kabupaten Musi Rawas Utara seperti: Dimensi Tangibel, formulir pengguna layanan memiliki standar yang jelas, kemampuan pegawai dalam menggunakan alat bantu dalam proses pelayanan serta konseling yang begitu sangat dibutuhkan masyarakat dapat terpenuhi dengan maksimal. Dimensi Assurance (Jaminan) telah terpenuhi dengan memberikan rasa percaya sebagai jaminan kepada masyarakat. Dimensi empathy, dimensi ini memberikan komunikasi yang baik, perhatian dan responsif yang tulus dan bersifat individual yang diberikan kepada penerima layanan dengan berupaya memahami penyedia layanan diharapkan memiliki suatu pengertian dan pengetahuan tentang pengguna layanan, memahami kebutuhan pengguna layanan secara personal dan humanis. Kata Kunci: Pelayanan Publik; Perlindungan Anak.